Phospholipid scramblase 1 amplifies anaphylactic reactions in vivo - Kassas-Guediri, Asma (PLoS One, 2017)
Mast cells are critical actors of hypersensitivity type I (allergic) reactions by the release of vasoactive and proinflammatory mediators following their activation by aggregation of the high-affinity receptor for immunoglobulin E (FcεRI). We have previously identified Phospholipid Scramblase 1 (PLSCR1) as a new molecular intermediate of FcεRI signaling that amplifies degranulation of the rat mast cell line RBL-2H3. Here we characterized primary mast cells from Plscr1(-/-) mice. The absence of PLSCR1 expression did not impact mast cell differentiation as evidenced by unaltered FcεRI expression, general morphology, amount of histamine stored and expression of FcεRI signal effector molecules. No detectable mast cell deficiency was observed in Plscr1(-/-) adult mice. In dose-response and time-course experiments, primary cultures of mast cells (bone marrow-derived mast cells and peritoneal cell-derived mast cells) generated from Plscr1(-/-) mice exhibited a reduced release of β-hexosaminidase upon FcεRI engagement as compared to their wild-type counterparts. In vivo, Plscr1(-/-) mice were protected in a model of passive systemic anaphylaxis when compared to wild-type mice, which was consistent with an observed decrease in the amounts of histamine released in the serum of Plscr1(-/-) mice during the reaction. Therefore, PLSCR1 aggravates anaphylactic reactions by increasing FcεRI-dependent mast cell degranulation. PLSCR1 could be a new therapeutic target in allergy.